GAMBARAN POLA KONSUMSI PANGAN KELUARGA PESERTA PROGRAM PERCEPATAN PENGANEKARAGAMAN KONSUMSI PANGAN DI KELURAHAN MABAR HILIR KECAMATAN MEDAN DELI TAHUN 2014 - Titin Herlina; Fitri Ardiani; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Patterns of food consumption group of Food Consumption Diversification Acceleration program which do not meet the recommended ideal composition characterized by a score of Desirable Dietary Pattern were low at 77, is below the target set by the government. The purpose of this research was to know describe the family food consumption patterns of the participants Food Consumption Diversification Acceleration program, in Mabar Hilir sub district, Medan Deli district, 2014. This research was a descriptive study by cross sectional research design. The population were families of Food Consumption Diversification Acceleration program for 30 families and then to be total sampling. Type data was using primary data and secondary data. Primary data (characteristic family, and pattern of food consumption family) was collected by food frequency, food recall and characteristic family form. Secondary data were about the location of this study has obtained from village office of Mabar Hilir while about Food Consumption Diversification Acceleration program has obtained from Food Security Agency, Medan. The results showed that the consumption of energy in medium category (50,00%), and consumption of protein in lower category (43,33%).The diversification of food consumption status of families are in the high category (90,00%) and medium category (10,00%). There needs to be an construction continuity for all members of the group Food Consumption Diversification Acceleration on the application of diverse food consumption. And family groups Food Consumption Diversification Acceleration to optimize their courtyards as a source of household food and consume foods with adequate amounts. Keywords: food consumption, food diversification, group of Food Consumption Diversification Acceleration